2002
DOI: 10.1093/rheumatology/41.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Computerized information‐gathering in specialist rheumatology clinics: an initial evaluation of an electronic version of the Short Form 36

Abstract: Computerized data collection is acceptable to patients and feasible in clinical settings. It provides responses that are at least comparable to those to the paper form, improves data capture and is available immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 13 publications
3
56
1
2
Order By: Relevance
“…Seventeen studies 104,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] published between 1994 and 2003 used SF-36. Not all studies reported all subscales.…”
Section: Meta-analysis Of Short Form Questionnaire-36 Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies 104,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] published between 1994 and 2003 used SF-36. Not all studies reported all subscales.…”
Section: Meta-analysis Of Short Form Questionnaire-36 Itemsmentioning
confidence: 99%
“…The impact of the different modes of using SF-36 was assessed using weighted pooled measures of agreement for within-subject comparisons and random-effects meta-analysis for between-subject comparison. There were seven studies 104,111,112,[114][115][116][117] that provided betweensubject comparisons only, eight studies [119][120][121][122][123][124][125][126] that provided within-subject comparisons only and two studies 113,118 that contributed data to both analyses. Table 15 summarises the information available from each study.…”
Section: Meta-analysis Of Short Form Questionnaire-36 Itemsmentioning
confidence: 99%
“…Along with the development of computer technologies, the technique of electronic data collection can dramatically reduce required time and costs, and a proper man-machine interface can still facilitate the completion of a survey for interviewees (Velikova et al, 1999;Ryan et al, 2002;Caro Sr et al, 2001;Drummond et al, 1995;Wilson et al, 2002). In some European and American countries, the technique of electronic data collection has already been applied in health-related quality of life (HRQoL) assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in many domains have demonstrated that computer administration of sensitive questions has been shown to increase reporting levels of sensitive behaviors, particularly in comparison with interviewer-based administration [73,74] as patients prefer and are more willing to disclose sensitive information to a computer rather than an interviewer [74][75][76][77][78][79][80][81][82][83][84][85][86][87]. Direct computer entry further enhances the quality of data by not allowing double or ambiguous answers [88], and it is often associated with a lower rate of unanswered questions than paper forms [80,82,85,88,89] because patients must provide a valid response to a question and/or press the "next" button to move on.Besides computer administration, several other alternatives to interviewer-based collection of adherence information are available. These include paper questionnaires, diaries, interactive voice response (IVR) calls, and text messaging.…”
mentioning
confidence: 99%